Perceived Comfort Meets Eco-Friendliness: How Perceived Attractiveness Influences Coffee Shop Brand Tumbler Users - Santy, Raeni Dwi; Harsanto, Firjatullah (International Journal of Magistravitae Management, 2024)
This study investigates the influence of perceived comfort on eco-friendliness among Starbucks tumbler users in Bandung, with perceived attractiveness serving as a mediating factor. Employing a quantitative approach that integrates descriptive and verificative research methods, the study aims to examine both the direct and indirect effects of perceived comfort on eco-friendliness through perceived attractiveness. Primary data were collected via questionnaires distributed to 100 Starbucks tumbler users in Bandung. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the SmartPLS software. The findings reveal that perceived comfort significantly influences eco-friendliness, both directly and indirectly, through perceived attractiveness. The implications of this research suggest that to enhance both environmental sustainability and product appeal, Starbucks and similar businesses should implement several strategies. These include diversifying payment methods (such as digital banking and e-commerce), ensuring that tumblers provide tangible practical benefits (such as temperature retention), and prioritizing ergonomic designs and eco-friendly materials to strengthen the product's market position. Ultimately, these measures will contribute to the development of more sustainable and appealing products, thereby fostering greater environmental awareness among consumers.